PENGARUH TRANSFER PRICING, DEWAN KOMISARIS INDEPENDEN DAN KEPEMILIKAN ASING TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI PRIMER YANG TERDAFTAR DI BEI PERIODE 2018-2022) - Madani, Dini Nur; Djohar, Chaidir (Publika Citra Media, 2024)
The aim of this research is to determine or test the influence of Transfer Pricing, Independent Board of Commissioners and Foreign Ownership on Tax Avoidance in primary consumer goods sector companies listed on the Indonesia Stock Exchange (BEI). The population of this research is all primary consumer goods industry companies listed on the Indonesia Stock Exchange during the period 2018 to 2022. The sample for this research was obtained using a purposive sampling method, where only 86 manufacturing companies listed on the Indonesia Stock Exchange met the criteria, so that 7 data were obtained. which was used as a research sample. The data source in this research was obtained from the Indonesian Stock Exchange website. This research uses a multiple regression model to test the influence of each variable on tax avoidance. From this research the results show that Transfer Pricing, Independent Board of Commissioners and Foreign Ownership have an influence on Tax avoidance.